EVE Online Newbie Guides: Helpful information or gatekeeping mechanisms at work? - Bergstrom, Kelly (AoIR Selected Papers of Internet Research, 2013)
_EVE Online_ is a space-themed Massively Multiplayer Online Game (MMOG) that has a reputation of having an exceptionally punishing learning curve. It has been argued that its difficulty stems from the in-game tutorial purposefully leaving out important information, forcing novice players to consult outside resources to be successful in this game. Through content analysis of player-created “newbie guides”, this paper argues that not only do the outside resources speak primarily to a particular demographic of player, their use of exclusionary language and imagery actively discourages participation from other demographics of potential players. 2 is a game whose player base is almost entirely composed of white males, and in this paper it is argued that these newbie guides are an example of a gatekeeping mechanism that works to maintain the exceptionally homogenous player community composition of this MMOG.